Ketumbar (Coriandrum sativum L.) sebagai Agen Antiinflamasi Alami: Studi Literatur - Ruben Ferdian; Susianti Susianti; Ratri Mauluti Larasati; Waluyo Rudiyanto (Medula, 2026)
Inflammation plays a crucial role in the pathogenesis of various chronic diseases, prompting continued interest in the development of natural anti-inflammatory agents with favorable efficacy and safety profiles. Coriandrum sativum L. (coriander) has been reported to exhibit anti-inflammatory properties through multiple biological pathways. This article aims to summarize and evaluate recent experimental evidence regarding the anti-inflammatory activity of Coriandrum sativum. A narrative review approach was employed, with literature searches conducted in PubMed and Google Scholar for publications from 2015 to 2025 using keywords related to Coriandrum sativum and inflammation. Included studies comprised in vitro and in vivo experiments assessing the anti-inflammatory effects of extracts, fractions, or active components of Coriandrum sativum, with extracted data covering the type of preparation, experimental model, dosage or concentration, and measured inflammatory parameters. The reviewed studies indicate that various preparations of Coriandrum sativum exhibit measurable anti-inflammatory activity, particularly polar extracts (ethanolic and methanolic) and essential oils rich in linalool, which were consistently reported to reduce pro-inflammatory mediators and cytokines and to improve biochemical and histopathological parameters in inflammatory models. Nevertheless, heterogeneity in methodologies, dosage variations, and limited phytochemical characterization were noted across studies. Based on the available evidence, polar extracts and essential oils of Coriandrum sativum appear to be the most promising preparations as natural anti-inflammatory agents; however, further studies focusing on extract standardization, toxicity evaluation, and early-phase clinical trials are required to support their potential application in humans.